The Cambridge companion to English Renaissance tragedy - Smith, Emma; Sullivan, Garrett A. Jr. ca. 20./21. Jh. (Cambridge companions to topics, 2010)
"Featuring essays by major international scholars, this Companion combines analysis of themes crucial to Renaissance tragedy with the interpretation of canonical and frequently taught texts. Part I introduces key topics, such as religion, revenge and the family, and discusses modern performance traditions on stage and screen. Bridging this section with Part II is a chapter which engages with Shakespeare. It tackles Shakespeare's generic distinctiveness and how our familiarity with Shakespearean tragedy affects our appreciation of the tragedies of his contemporaries. Individual essays in Part II introduce and contribute to important critical conversations about specific tragedies. Topics include The Revenger's Tragedy and the theatrics of original sin, Arden of Faversham and the preternatural, and The Duchess of Malfi and the erotics of literary form. Providing fresh readings of key texts, the Companion is an essential guide for all students of Renaissance tragedy"--